2003
DOI: 10.1136/tc.12.suppl_2.ii67
|View full text |Cite
|
Sign up to set email alerts
|

How has the prevalence of cigarette smoking changed among Australian adults? Trends in smoking prevalence between 1980 and 2001

Abstract: Objective: To examine trends in the prevalence of cigarette smoking between 1980 and 2001 among several different sociodemographic groups within the Australian population. Method: National cross sectional surveys conducted by face to face interview every 3 years from 1980. Respondents were classified into five age groups and the occupation of respondents in the workforce were classified into one of upper or lower white collar or upper or lower blue collar. Main outcome measure: Prevalence of smoking at least w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 19 publications
13
98
1
Order By: Relevance
“…Low SES groups are more vulnerable to the tobacco epidemic even in high income countries (7)(8)(9)(10)(11)(12). The common reported reasons are high stress, low literacy and poor social capital among these individuals (7)(8)(9)(10)(11)(12).…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 3 more Smart Citations
“…Low SES groups are more vulnerable to the tobacco epidemic even in high income countries (7)(8)(9)(10)(11)(12). The common reported reasons are high stress, low literacy and poor social capital among these individuals (7)(8)(9)(10)(11)(12).…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Tobacco industry internal documents show how opportunity to attract these potential users with targeted marketing are exploited (13). Multiple observational studies have shown that the rate of tobacco cessation is also not uniform within countries, more deprived socioeconomic groups show almost half the rate of decline as compared with the less deprived groups (7)(8)(9)(10)(11)(12). This underscores that tobacco control efforts need to be targeted to these most vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Population-based tobacco control strategies, such as taxing cigarettes, banning advertising and restricting the areas where people can smoke, have halved cigarette smoking in Australia (White, Hill, Siahpush, & Bobevski, 2003) and the US (Pierce et al, 1998) over the past three decades. These strategies are much more effective and efficient than strategies that focus only on addicted persons, or persons at high risks of developing addiction (Rose, 1992;Vos et al, 2010).…”
Section: Compulsory Addiction Treatment For Paternalistic Reasonsmentioning
confidence: 99%